Pressure vessel design simulation using hybrid harmony search algorithm - Alaa A., Alomoush; Mohammed I., Younis; Khalid S., Aloufi; Alsewari, Abdulrahman A.; Kamal Z., Zamli (Universiti Malaysia Pahang, 2019)
Recently the development of optimization algorithm is rapidly increased. Among several optimization algorithms, Harmony Search (HS) has been recently proposed for solving engineering optimization problems. The HS has some weaknesses such as parameters selection and falling in local optima. Many variants proposed to solve these problems. This paper presents successful hybrid algorithms with high performance to solve the pressure vessel design simulation. The hybrid algorithms consist of well-known variants of HS and an opposition-based learning technique. The hybrid algorithm improved the HS exploration and avoiding falling in local optima, which lead the algorithm to provide significant results.